2008
DOI: 10.1080/01421590701784356
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ cognitive and affective attitudes towards learning and using communication skills – a nationwide cross-sectional study

Abstract: Medical students have positive attitudes towards learning and using communication skills. Cognitive and affective attitudes displayed different patterns. Being female and having worked in the health services before admission to the medical school predicted more positive scores both towards cognitive and affective attitudes. Having worked as a junior doctor during medical school predicted more positive cognitive attitudes. Cognitive attitudes towards communication skills did not vary significantly between year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
51
3
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 39 publications
8
51
3
3
Order By: Relevance
“…A Norwegian study showed a positive correlation between students' attitudes towards learning communication skills and previous work experience (Anvik et al 2008), thus supporting our findings.…”
Section: Comments On Resultssupporting
confidence: 90%
“…A Norwegian study showed a positive correlation between students' attitudes towards learning communication skills and previous work experience (Anvik et al 2008), thus supporting our findings.…”
Section: Comments On Resultssupporting
confidence: 90%
“…The comparative analysis indicated that emphasising within this training the importance of compassion, friendliness and integrity in the practitioner/client interaction will be valuable to new graduates. The artificial nature of the role play scenarios used was mentioned in the qualitative data emphasising the importance of context and experiential learning which is described extensively in the medical education literature [23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…Further understanding and benchmarking are important as differences between perceptions and teaching outcomes may, to some extent, be linked to variations in teaching methods and/or curriculum design, and can help pharmacy educators find new ways of improving and refining teaching in pharmacy schools. [26][27][28] This study aimed to describe Nordic pharmacy students' opinions of their PCST, and the association between course leaders' reports of PCST qualities (eg, amount of teacher-led training, numbers of experiential training methods) and students' perceptions of their training (eg, sufficient training, improvement of communication ability). The second objective was to determine what factors influence these associations.…”
mentioning
confidence: 99%